The results of neuropathic forms diabetic foot treatment with lipoic acid preparations - M. M. Mursalov (Лечащий Врач)
The results of treatment of 123 patients with diabetic foot syndrome were analyzed. According to modern concepts, the leading cause of the development of diabetic foot syndrome and subsequent amputation is diabetic polyneuropathy of the lower extremities. The latter and associated foot deformities, as well as the loss of protective pain sensitivity, lead to spontaneous ulcerative defects in the soft tissues of the foot with their further infection and the development of a purulent-necrotic process. Their dermographic data, anamnesis, clinical manifestations and the course of the disease, the state of compensation of carbohydrate and lipid metabolism were studied. The severity of neuropathy, its clinical manifestations, the presence of ulcerative-necrotic lesions, their origin, the presence of concomitant macroangiopathy of the lower extremities, the condition of the bones of the foot, the presence of manifestations of microangiopathy were determined. A study was also conducted on the effectiveness and tolerability of patients with different doses of alpha-lipoic acid preparations (600, 900 and 1200 mg per day), which was used for the etiotropic treatment of neuropathy. The effect of alpha-lipoic acid on the treatment of diabetic neuropathy in patients suffering from purulent-necrotic forms of diabetic foot syndrome was studied. The high efficiency of the use of this group of drugs, both in standard and in increased doses, has been established. The study demonstrated that parenteral administration of alpha-lipoic acid preparations, both at a dose of 600 mg, and 900 and 1200 mg per day, is equally well tolerated by patients, does not cause significantly significant side effects and allows us to recommend the use of this group of drugs intravenously, followed by the use of 600 mg /day orally in the treatment of patients with diabetic foot syndrome complicated by ulcerative necrotic process.